ANIMATING IDENTITY: A DISCOURSE ANALYSIS OF PAK-PAK FOLKLORE IN LOCALIZED DIGITAL TEACHING MATERIALS - Simbolon, Sanris Lawanti; Ansari, Khairil; Harahap, Muharrina (ppjbsip, 2025)
This study explores the development of localized digital teaching materials using animated Pak-Pak folklore, reframed through a discourse analysis perspective. While the current research focuses on the pedagogical benefits of animation in enhancing students understanding and engagement with local culture, this paper extends the discussion by analyzing the discursive elements embedded in storytelling, teacher narration, and student interpretation. Using qualitative methodsliterature analysis, classroom observation, interviews, and student responsesthe study examines how folklore as discourse transmits cultural values, shapes identity, and promotes moral reasoning in eighth-grade classrooms. Results indicate that animation enhances comprehension of narrative elements, such as setting, characters, and values. More importantly, students engage in reflective discussions where values like courage, honesty, and cooperation are expressed and negotiated in their own language. Teachers also act as discourse mediators, framing cultural messages through narration and prompting. The study shows that discourse, visual storytelling, and interactivity work together to turn folklore into a living cultural experience rather than static heritage. Despite challenges such as limited teacher digital skills and infrastructure gaps, the findings highlight the promise of integrating discourse-sensitive animated materials into the Merdeka Curriculum. Future research is recommended to explore how localized narratives in digital formats influence language use, value expression, and cultural identity formation in various Indonesian classrooms. This approach contributes to both educational media development and critical discourse studies by bridging visual literacy, cultural storytelling, and classroom interaction.